Optimasi Manajemen Keterlambatan Pengadaan Komponen Mengunakan Root Cause Analysis di Perusahaan Manufaktur - Sukhron Makhmudah; Fibi Eko Putra; Puput Rahmawati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze and optimize the management of component procurement delays in a manufacturing company, using the Root Cause Analysis (RCA) approach. The research was conducted on procurement delay data for the period March to July 2024, which recorded 226 cases, of which 167 cases were further analyzed based on the six main sub-components that had the highest delay rates. The Fishbone Diagram and 5 Why's methods, as part of the RCA, were used to identify the root causes of the delays, including lack of internal coordination, unintegrated information systems, and the characteristics of suppliers who are not ready to stock (make-to-order). The results of the analysis show that improvement strategies can focus on developing risk-based procurement SOPs, periodically evaluating supplier performance, and developing an integrated information system. Implementation of these proposals is believed to significantly reduce the frequency of delays and improve procurement efficiency. The findings are expected to be a reference in improving supply chain management in manufacturing companies with similar characteristics